Prediction of intramammary infection status across the dry period from lifetime cow records - Henderson, A.C.; Hudson, C.D.; Bradley, Andrew J.; Sherwin, V.E.; Green, Martin J. (American Dairy Science Association, 2016)
The dry period is very important for mammary gland health, with the aim not only to cure existing intramammary infections (IMI) but also to prevent new IMI. Although it is known that the dry period is an important time for optimizing udder health, the probability that individual cows will succumb to a new IMI or, if infected, will fail to cure an IMI is not well established. The aim of this study was to investigate whether lifetime cow data, available through routine on-farm milk recording, could be used to predict changes in IMI status across the dry period for individual cows that were (1) deemed high somatic cell count (SCC; >199,000 cells/mL) or (2) low SCC (<200,000 cells/mL) at the last test day before drying off. Milk recording data collected between September 1994 and July 2014 from 114 herds in the United Kingdom were used. Two 2-level random effects models were built and both cure and new IMI were used as outcome variables in separate models. Cows with a smaller proportion of test days with a high SCC in the lactation before drying off, a smaller proportion of test days recording a high SCC in the lactation before the current lactation, of lower parity, producing less milk before drying off, of lower days in milk at drying off, and of lower SCC just before drying off were more likely to cure across the dry period. Dry period length had no effect on the likelihood of cure. Individual cows with a smaller proportion of test days recording a high SCC in the lactation before the current, of lower parity, of lower milk production at drying off, and fewer days in milk at drying off were less likely to develop a new IMI. Dry period length was found to have no effect on the probability of new IMI. Model predictions showed that a high level of discrimination was possible between cows with a high and low risk of both cures and new infections across the dry period.